Assessing and Managing Professional Quality of Life Among Nurses in the Face of Pandemic Challenges - Ilfa Khairina; Esthika Ariany Maisa; Dally Rahman (NurseLine Journal, 2024)
The rapid adaptation of health services significantly burdens healthcare professionals, especially nurses. It is crucial to balance healthcare professionals' professional quality of life with their fatigue and stress levels. The study aims to assess nurses' professional quality of life, particularly in the context of the challenges posed by the COVID-19 pandemic. The researchers aim to understand the levels of compassion satisfaction, burnout, and secondary traumatic stress experienced by nurses in Padang City hospitals. Employing a descriptive design with a cross-sectional methodology, this study aims to portray nurses' professional quality of life by concurrently assessing compassion satisfaction, burnout, and the level of secondary traumatic stress using the Perceived Stress Scale and the Professional Quality of Life Scale (ProQoL-21). Eighty-eight nurses participated in this study and were selected using purposive sampling techniques between August and November 2023. This study revealed that 54.5% of respondents reported a moderate level of compassion satisfaction related to COVID-19, 68.2% experienced a moderate level of burnout, and 40.9% had a moderate level of secondary traumatic stress.